Massage Therapy to Relieve Menopausal Symptoms: A Systematic Review - Eka Listiana; Anggorowati Anggorowati; Dwi Susilawati (Universitas Muhammadiyah Semarang, 2022)
Objective: This study aims to analyze the duration, time, and results of massage therapy in reducing symptoms of menopause. Methods: A systematic review through maternity nursing articles to analyze the effects of massage therapy in reducing menopausal symptoms. The inclusion criteria in this study are 1) related articles about massage therapy. 2) Articles that contain interventions used in reducing menopausal symptoms. 3) Articles use English in writing. 4) Articles published after 2010. 5) Articles published have a complete section. Search articles using electronic databases namely Sciene Direct, Pubmed, PMC, Google Schoolar and Scopus. Articles that meet the inclusion criteria will be collected and analyzed systematically. Results: In a systematic review it is explained that massage therapy can reduce menopausal symptoms but in the location and duration of the intervention still need consideration from further researchers. Conclusion: Based on the results of the study, massage therapy carried out in the back area is recommended to reduce menopausal symptoms.